Ischemic stroke review - Nepal - Joshi, Dipesh Mangal; Maharjan, Rony (Journal of General Practice and Emergency Medicine of Nepal, 2021)
The prevalence of stroke in the Nepalese population over the years has shifted from a higher age group, over  60 years to below 45 years of age, most common being ischemic stroke with the cardioembolic origin and  predominantly in the male population. Smoking, diabetes, hypertension, dyslipidemia are the main predisposing factors. A very small percentage of patients (5-20%) presenting in the emergency department is thrombolysis eligible due to late arrival to which lockdown also has some effect. Endovascular recanalization has also shown good outcomes. Complications of stroke included aspiration pneumonia. Mortality was more in patients with low Glasgow Coma Scale (GCS) at presentation and was not affected by the presence of Atrial Fibrillation. National Institutes of Health Stroke Scale (NIHSS) score is reliable and can be used to predict outcomes.